2018
DOI: 10.1038/s41598-018-32486-z
|View full text |Cite
|
Sign up to set email alerts
|

Thienoisoindigo-Based Semiconductor Nanowires Assembled with 2-Bromobenzaldehyde via Both Halogen and Chalcogen Bonding

Abstract: We fabricated nanowires of a conjugated oligomer and applied them to organic field-effect transistors (OFETs). The supramolecular assemblies of a thienoisoindigo-based small molecular organic semiconductor (TIIG-Bz) were prepared by co-precipitation with 2-bromobenzaldehyde (2-BBA) via a combination of halogen bonding (XB) between the bromide in 2-BBA and electron-donor groups in TIIG-Bz, and chalcogen bonding (CB) between the aldehyde in 2-BBA and sulfur in TIIG-Bz. It was found that 2-BBA could be incorporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…To start with the fluorinated polymer series, it is worth noting that solubility decreases with increasing number of fluorine atoms on the benzothiadiazole unit. This is due to the many weak bonds created between fluorine atoms and neighboring heteroatoms. In practice, by lowering the temperature, the progressive aggregation of the polymer is observed and consequently, the UV–visible absorption of the solution is more and more similar to the one recorded for thin films. This is clearly observable for PF 2 that exhibits already at 65 °C and below (Figure c), typical thin film-like absorption spectra.…”
Section: Resultsmentioning
confidence: 99%
“…To start with the fluorinated polymer series, it is worth noting that solubility decreases with increasing number of fluorine atoms on the benzothiadiazole unit. This is due to the many weak bonds created between fluorine atoms and neighboring heteroatoms. In practice, by lowering the temperature, the progressive aggregation of the polymer is observed and consequently, the UV–visible absorption of the solution is more and more similar to the one recorded for thin films. This is clearly observable for PF 2 that exhibits already at 65 °C and below (Figure c), typical thin film-like absorption spectra.…”
Section: Resultsmentioning
confidence: 99%
“…90 Among nanomaterials, a 2018 study from Noh et dehyde (XB donor) for the assembly of 1D nanowires that were used to construct OFET devices with favorable charge transport. 91 A related publication in 2020 from Koo et al demonstrated improved charge transport in a diketopyrrolopyrrole-dithienothiophene conjugated polymer by doping 2-bromobenzaldehyde (XB donor) to enhance through-space alignment of polymer backbones. 92 A series of studies from the group of Fabien Silly have described self-assembly of star-shaped oligophenylenes on metal and graphite where XX interactions can selectively pattern surfaces and tune band gap.…”
Section: ■ Halogen-bonding Interactions: 2dmentioning
confidence: 99%
“…Among nanomaterials, a 2018 study from Noh et al. employed XB between a thienoisoindigo-based chromophore and 2-bromobenzaldehyde (XB donor) for the assembly of 1D nanowires that were used to construct OFET devices with favorable charge transport . A related publication in 2020 from Koo et al demonstrated improved charge transport in a diketopyrrolopyrrole-dithienothiophene conjugated polymer by doping 2-bromobenzaldehyde (XB donor) to enhance through-space alignment of polymer backbones .…”
Section: Halogen-bonding Interactions: 2d Control and Structural Modu...mentioning
confidence: 99%
“…For example, charge transport efficiency in FETs can be significantly improved when conjugated backbones are assembled in one-dimensional (1D) nanowires, nanorods, or nanofibers due to the increased intermolecular charge transport. 27 29 In addition, intermolecular electron delocalization can narrow the band gaps of conjugated polymers, thereby enlarging the range of light absorption in the visible and NIR regions, thus enhancing light harvesting efficiency, which is useful when conjugated polymers are used as a photosensitizer in photocatalysis applications. 30 32 …”
Section: Introductionmentioning
confidence: 99%